Legal Framework and Law Enforcement of Illegal Mining in Indonesia: A Normative Jurisdictional Analysis of the Implications of Environmental Law and Criminal Law - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Santoso, Bagus Teguh; Kunarso, Kunarso (West Science Law and Human Rights, 2025)
This paper explores the legal framework and law enforcement mechanisms regarding illegal mining in Indonesia, focusing on the implications for environmental protection and criminal accountability. The study employs a normative juridical analysis to examine the existing laws, including the Mining Law No. 4 of 2009, Environmental Law No. 32 of 2009, and the Indonesian Criminal Code (KUHP). The paper highlights the gaps in the legal system, such as weak enforcement, inadequate penalties, and the challenges posed by corruption within local authorities. It also assesses the social and environmental consequences of illegal mining, including deforestation, pollution, and the exploitation of local communities. The findings suggest that while Indonesia has a comprehensive legal framework, the effectiveness of its enforcement mechanisms remains insufficient. Based on the analysis, the paper proposes recommendations to strengthen law enforcement, improve penalties, combat corruption, and support alternative livelihoods for communities affected by illegal mining.